Optimization of Bacillus aerius strain JS-786 cell dry mass and its antifungal activity against Botrytis cinerea using response surface methodology - Shafi, Jamil; Mingshan, Ji; Zhiqiu, Qi; Xiuwei, Li; Zumin, Gu; Xinghai, Li; Yang, Zhang; Peiwen, Qin; Hongzhe, Tian; Wunan, Che; Kai, Wang (Archives of Biological Sciences, 2017)
The optimization of fermentation conditions is necessary for field application of biological control agents. The present study was designed to optimize the fermentation conditions for the Bacillus aerius strain, JS-786 in terms of cell dry mass and its antifungal activity against Botrytis cinerea with response surface methodology. A strain of bacteria with strong antifungal activity was isolated from the phyllosphere of tomato plant and identified as B. aerius JS-786 based on the sequence homology of its 16S rRNA gene. After the success of preliminary antifungal activity tests, response surface methodology was used to optimize the fermentation conditions (medium pH, gelatin percentage, incubation period, rotatory speed and incubation temperature) to maximize the cell dry mass and antifungal activity against B. cinerea. A 25 factorial central composite design was employed and multiple response optimization was used to determine the desirability of the operation. The results of regression analysis showed that at the individual level, all of the experimental parameters were significant for cell dry mass; significant results were obtained for antifungal activity pH, incubation period, rotatory speed and incubation temperature. The interactive effect of the incubation period, rotatory speed and incubation temperature was significant. Maximum cell dry mass (8.7 g/L) and inhibition zone (30.4 mm) were obtained at pH 6.4, gelatin 3.2%, incubation period 36.92 h, rotatory speed 163 rpm, and temperature 33.5°C. This study should help to formulate a more rational and cost-effective biological product both in terms of bacterial growth and antifungal activity. https://doi.org/10.2298/ABS160421122S Received: April 21, 2016; Revised: May 27, 2016; Accepted: June 17, 2016; Published online: November 7, 2016 How to cite: Shafi J, Mingshan J, Zhiqiu Q, Xiuwei L, Zumin G, Xinghai L, Yang Z, Peiwen Q, Hongzhe T, Wunan C, Kai W. Optimization of bacillus aerius strain JS-786 cell dry mass and its antifungal activity against botrytis cinerea using response surface methodology. Arch Biol Sci. 2017;69(3):469-80.